Comparison of Concepts and Practices of Citizenship Between Liberal Democracy and Pancasila Democracy - Abdul Basit (Pancasila: Jurnal Keindonesiaan, 2023)
This research focuses on how the existence of the world's great ideologies is between liberal ideology and Pancasila ideology. These two ideologies are studied and analyzed in depth, especially concerning conceptions and practices that lead to the existence of a democratic system in a country such as the United States and Indonesia. This study uses a qualitative approach with library research methods. The data collection technique uses documentation, while the data analysis used is content analysis. The results of this study indicate that the existence of the two world's great conceptions such as liberal democracy and Pancasila democracy remains the subject of a very long scientific discourse into the 21st century as it is today. The practice of liberal democracy and Pancasila plays its role according to the culture of each country. If liberal democracy focuses on the process of freedom and equality as happened in the United States and almost all European countries. In contrast to liberal democracy, Pancasila democracy is of serious concern to the people of Indonesia in which religion, culture, and the state constitution are integrated into one unit so that the political system of the nation and state of Indonesia runs as it should following the values of Pancasila and the 1945 Constitution of the Republic of Indonesia.